On the effects of tube butting on the structural performance of steel bicycle frames - Covill, D.; Drouet, J.-M. (Proceedings, 2018)
Previous studies have shown how finite element analysis (FEA) can be used to support designers and frame builders in the selection of butted tubes to tune the stiffness and strength behaviour of steel bicycles. The aim of this paper was therefore to analyse the effects of tube butting on the stiffness, stress distribution and energy absorption behaviour of bicycle frames using numerical simulations. Butted tubes were shown to provide a highly effective means to decrease mass whilst producing a disproportionately small change in stress compared with a straight gauge tubeset with a maximum material condition although there was no added benefit in terms of stiffness or strain energy. Conversely, decreasing the wall thickness produced an increase in stress at the tube ends that was disproportionate to the change in mass. This work can now be extended to analyse a fuller set of butted profiles for a range of tube types.